2001
DOI: 10.1182/blood.v97.9.2618
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal expression of CD38 and CD34 by adult murine hematopoietic stem cells

Abstract: The effects of activation of adult murine stem cells on their expression of CD38 were studied using a murine transplantation model. First, the published finding that the majority of long-term engrafting cells from normal adult steady-state marrow are CD38 ؉ was confirmed. Next, it was determined that the majority of stem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 18 publications
2
48
1
Order By: Relevance
“…This direction of changes is opposite to that of the changes seen in adult HSCs. 6 Earlier, Randall et al 7 demonstrated that only CD38 high population, but not CD38 − population, in Sca1 + , c-kit + , Lin low/− liver cells from 14.5 days post coitum (dpc) mice and adult mice are capable of long-term hematopoietic reconstitution. Dagher et al 8 also demonstrated that only CD38 + population in c-kit + , Lin − yolk sac cells derived from 9 dpc mice, as well as adult mice are capable of long-term reconstitution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This direction of changes is opposite to that of the changes seen in adult HSCs. 6 Earlier, Randall et al 7 demonstrated that only CD38 high population, but not CD38 − population, in Sca1 + , c-kit + , Lin low/− liver cells from 14.5 days post coitum (dpc) mice and adult mice are capable of long-term hematopoietic reconstitution. Dagher et al 8 also demonstrated that only CD38 + population in c-kit + , Lin − yolk sac cells derived from 9 dpc mice, as well as adult mice are capable of long-term reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…6 To determine whether there are similar effects on stem cells in 5-week-old mice, we tested CD38 expression by HSCs of 5-week-old mice following 5-FU injection. Because the effects of 5-FU injection on the expression of CD34 by HSCs in 5-week-old mice are not known, we separated bone marrow cells on the basis of CD38 expression Leukemia alone.…”
Section: Cd38 Expression By Hscs Of 5-fu-treated 5-week-old Micementioning
confidence: 99%
See 2 more Smart Citations
“…We prepared partially purified stem cell-enriched BMCs as previously described [26][27][28]. Briefly, 5-fluorouracil (Kyowa Hakko Kogyo; Tokyo, Japan) was injected into the peritoneal cavity of 4-week-old male Brown Norway rats (Clea Japan; Osaka, Japan) at 150 mg/kg body weight 48 hours before sacrifice.…”
Section: Preparation Of Stem Cell-enriched Bmcs For Graftingmentioning
confidence: 99%